2013
DOI: 10.1073/pnas.1313474110
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin binding mechanism and disease-causing mutations in Munc18-2

Abstract: Significance Understanding the molecular mechanisms that control secretion from cytotoxic T lymphocytes (CTL) and natural killer (NK) cells is the key for understanding how these cells destroy virally infected and tumourigenic cells. Precisely how mutations in Munc18-2 and syntaxin 11 (Stx11) give rise to loss of CTL and NK function and severe immunodeficiency is poorly understood. In this study we present a crystal structure of human Munc18-2 and analyze the disease-causing mutations. Our findings r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 72 publications
8
84
1
Order By: Relevance
“…2A). Consistently, addition of Munc18-2 E132A -a Munc18-2 disease-associated mutant also located within the N lobe of Munc18-2 that reduced binding to STX11 (34,35)-had no effect on the extent of lipid mixing or complete fusion mediated by either STX11-GPI or STX11 H3 -GPI ( Fig. 2A).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…2A). Consistently, addition of Munc18-2 E132A -a Munc18-2 disease-associated mutant also located within the N lobe of Munc18-2 that reduced binding to STX11 (34,35)-had no effect on the extent of lipid mixing or complete fusion mediated by either STX11-GPI or STX11 H3 -GPI ( Fig. 2A).…”
Section: Resultssupporting
confidence: 60%
“…Previous studies have suggested that Munc18-2 can interact with the monomeric Syntaxins STX3 (39,40), STX2 (41), and STX11 (13,(33)(34)(35). However, other SM proteins have distinct binding modes in which they engage either monomeric syntaxins or SNARE complexes (42-45).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Munc18-1 and Munc18-2 are known to bind to syntaxin-2 and syntaxin-3 in addition to syntaxin-11 and neuronal syntaxin-1 (Riento et al, 1998;Tamori et al, 1998). Recent work suggested that syntaxin-3 potentially substitutes for the function of syntaxin-11 in syntaxin-11-deficient mast cells (Hackmann et al, 2013). Thus, we examined a possible change of syntaxin-3 levels in our Munc18-1/2 DKD mast cells, by using a recently generated rabbit monoclonal anti-syntaxin-3 antibody (EPR8543, Abcam).…”
Section: Munc18 Proteins Regulate Expression Levels Of Syntaxin-3 Andmentioning
confidence: 99%
“…However, a recent NMR study on full length Sx1a, including its TMD, reported a higher proportion of the open Sx1a conformation than was observed using the soluble cytosolic domain of Sx1a (Dawidowski & Cafiso, 2013 Although its precise role remains controversial, the importance of SM proteins in disease has been well documented. For example, mutations in Munc18a have been linked with early infantile epileptic encephalopathy (Saitsu et al, 2008(Saitsu et al, , 2010 and Munc18b mutations can result in familial hemophagocytic lymphohistiocytosis type 5 (Cô te et al, 2009;Hackmann et al, 2013). This link between SM proteins and disease has also been confirmed by mutagenesis studies in mice, where deletion of Munc18-1 in mice leads to a complete loss of neurotransmitter secretion from synaptic vesicles throughout development (Verhage et al, 2000).…”
Section: Introductionmentioning
confidence: 87%